1987
DOI: 10.1159/000124811
|View full text |Cite
|
Sign up to set email alerts
|

The Corticotropin-Releasing Factor Release in Rat Hypophysial Portal Blood Is Mediated by Brain Catecholamines

Abstract: In order to study the involvement of the hypothalamic corticotropin-releasing factor (CRF) in catecholamine-induced adrenocorticotropin (ACTH) secretion, we have measured CRF levels in rat hypophysial portal blood (HPB) after the pharmacological destruction of the ventral noradrenergic bundle (VNAB), using 6-hydroxydopamine (6-OHDA) stereotaxically injected into the VNAB. CRF levels in HPB were measured by radioimmunoassay, and the effects of 6-OHDA injection were controlled by the determination of catecholami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 16 publications
7
46
0
Order By: Relevance
“…These observations suggest that the IIH-induced CRF and AVP release into HPB is mediated through extrahypothalamic pathways. We and others have shown recently that central catecholamines, originating from the brainstem nuclei, have a stimulatory effect on hypothalamic CRF secretion in the rat (27,28). Interestingly, hypothalamic norepinephrine activity is increased during IIH in rats, and this increase parallels the variation in plasma corticosterone (29).…”
Section: Ram N 566mentioning
confidence: 70%
“…These observations suggest that the IIH-induced CRF and AVP release into HPB is mediated through extrahypothalamic pathways. We and others have shown recently that central catecholamines, originating from the brainstem nuclei, have a stimulatory effect on hypothalamic CRF secretion in the rat (27,28). Interestingly, hypothalamic norepinephrine activity is increased during IIH in rats, and this increase parallels the variation in plasma corticosterone (29).…”
Section: Ram N 566mentioning
confidence: 70%
“…Furthermore, catecholamines are known to influence the activity of neurons in the brain including the PGi and the CNA (Clayton and Williams, 2000;Williams et al, 2000). The PGi and CNA are enriched with corticotropin releasing factor (CRF) synthesizing neurons (Swanson et al, 1983;Herbert and Saper, 1990;Grigson et al, 1997a;Van Bockstaele et al, 1998b;Van Bockstaele et al, 1999) and it has been shown that norepinephrine influences the release of CRF (Guillaume et al, 1987;Koob, 1999) and adrenocorticotrophic hormone (Szafarczyk et al, 1987). Taken together, NTS neurons may coordinate the autonomic regulation of the limbic and amygdalar brain regions via targeting CRF neurons in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the monoamines controlling CRF and AVP are noradrenaline and 5-hydroxytryptamine. Lesioning of these monoaminergic pathways [4][5][6] or modification of 5-HT activity [7] alters the release of CRF in animal models.…”
Section: Introductionmentioning
confidence: 99%